Free Thyroxine Levels are Associated with Cold Induced Thermogenesis in Healthy Euthyroid Individuals - Maushart, Claudia Irene; Senn, Jaël Rut; Loeliger, Rahel Catherina; Kraenzlin, Marius E.; Müller, Julian; Becker, Anton S.; Balaz, Miroslav; Wolfrum, Christian; Burger, Irene A.; Betz, Matthias Johannes (Frontiers in Endocrinology, 2021)
Thyroid hormone (TH) is an important regulator of mammalian metabolism and facilitates cold induced thermogenesis (CIT) in brown adipose tissue (BAT). Profound hypothyroidism or hyperthyroidism lead to alterations in BAT function and CIT. In euthyroid humans the inter-individual variation of thyroid hormones is relatively large. Therefore, we investigated whether levels of free thyroxine (T4) or free triiodothyronine (T3) are positively associated with CIT in euthyroid individuals. We performed an observational study in 79 healthy, euthyroid volunteers (mean age 25.6 years, mean BMI 23.0 kg · m-2). Resting energy expenditure (REE) was measured by indirect calorimetry during warm conditions (EEwarm) and after a mild cold stimulus of two hours (EEcold). CIT was calculated as the difference between EEcold and EEwarm. BAT activity was assessed by 18F-FDG-PET after a mild cold stimulus in a subset of 26 participants. EEcold and CIT were significantly related to levels of free T4 (R2=0.11, p=0.0025 and R2=0.13, p=0.0011, respectively) but not to free T3 and TSH. Cold induced BAT activity was also associated with levels of free T4 (R2=0.21, p=0.018). CIT was approximately fourfold higher in participants in the highest tertile of free T4 as compared to the lowest tertile. Additionally, free T4 was weakly, albeit significantly associated with outdoor temperature seven days prior to the respective study visit (R2=0.06, p=0.037). These finding suggests that variations in thyroid hormone levels within the euthyroid range are related to the capability to adapt to cool temperatures and affect energy balance.